15-PGDH inhibition promotes muscle repair and strength recovery during GLP-1 receptor agonist–induced weight loss - Minas Nalbandian; Jameel Lone; Emmeran Le Moal; Ireh Kim; Kaitlin Jeuris; Yutong Kelly Li; Peggy Kraft; Meng Zhao; Kassie Koleckar; Zeyuan Zhang; Katrin J. Svensson; Helen M. Blau (Proceedings of the National Academy of Sciences, 2026)
Glucagon-like peptide-1 receptor agonists, including long-acting semaglutide, are transformative anti-obesity therapies. However, emerging evidence indicates that weight loss may come at the expense of skeletal muscle mass, a tissue essential for mobility, metabolic regulation, and overall health. Here, we show that inhibition of the gerozyme 15-hydroxyprostaglandin dehydrogenase (15-PGDH), a prostaglandin-degrading enzyme that increases with injury and aging, improves muscle repair and strength recovery in the presence of semaglutide. In a high fat diet-induced mouse model of obesity, semaglutide alone caused significant loss of muscle mass, while preserving contractile function. Following injury, obese mice exhibited pathological calcifications previously reported for the heritable myopathy, Duchenne Muscular Dystrophy. Semaglutide had both beneficial and deleterious effects, reducing calcific remodeling, but causing reduced regenerated myofiber sizes. This impaired regenerative myofiber growth in semaglutide-treated mice was surmounted by cotreatment with a 15-PGDH inhibitor (PGDHi), which stimulated muscle stem cell function and myofiber growth, leading to enhanced strength. Importantly, PGDHi synergizes with semaglutide to boost postinjury muscle quality and muscle force without compromising weight loss.